The potency of Pentagamavunone‐0 (PGV‐0) as chemopreventive agent for the formation and growth of breast cancer as revealed in 3D model - Wulandari Wulandari; Muthi’ Ikawati; Edy Meiyanto (Indonesian Journal of Biotechnology, 2020)
Pentagamavunone‐0 (PGV‐0) or 2,5‐bis(4’‐hydroxy‐3‐methoxybenzylidine)‐cyclopentanone is a curcumin analogue that exhibits anticancer activity in breast cancer cells. However, most of previous reports are limited to the use of two‐dimensional (2D) cell culture. The use of three‐dimensional (3D) cell culture model in cancer research can represent the real condition of cancer growth in patients better than the 2D culture. The purpose of this study was to determine the anticancer activity of PGV‐0 on a 3D model of HCC 1954 breast cancer cells. HCC 1954 cells were grown in the 3D culture in the presence of PGV‐0, and the spheroid formation and growth of formed spheroids were observed using microscope at 24 and 96 h, respectively. The cytotoxic effects were measured by MTT assay. PGV‐0 inhibited the formation and growth of spheroids at the concentration as low as 60 µM. The cytotoxic effect of PGV‐0 appeared in a dose‐dependent manner with the IC50 value of 70.9 µM. The results of this study indicate that PGV‐0 has an anticancer activity on a 3D model of HCC 1954 breast cancer cell line. Therefore, the result supported the potency of PGV‐0 as cancer chemopreventive agent.